2015
DOI: 10.1016/j.humpath.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Classification of microvascular patterns via cluster analysis reveals their prognostic significance in glioblastoma

Abstract: There are limited researches focusing on microvascular patterns (MVPs) in human glioblastoma and their prognostic impact. We evaluated MVPs of 78 glioblastomas by CD34/periodic acid-Schiff dual staining and by cluster analysis of the percentage of microvascular area for distinct microvascular formations. The distribution of 5 types of basic microvascular formations, that is, microvascular sprouting (MS), vascular cluster (VC), vascular garland (VG), glomeruloid vascular proliferation (GVP), and vasculogenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
4
36
0
5
Order By: Relevance
“…35 Again, different counting and labeling methods does not allow a direct comparison between our results and those previously obtained in the literature. On the other hand, we observed that MPNSTs with greater MVD in the periphery carry a worse prognosis, an issue previously demonstrated in astrocytomas, 46 glioblastomas, 47 prostate carcinomas, 48 and colorectal carcinomas. 49…”
Section: Discussionsupporting
confidence: 62%
“…35 Again, different counting and labeling methods does not allow a direct comparison between our results and those previously obtained in the literature. On the other hand, we observed that MPNSTs with greater MVD in the periphery carry a worse prognosis, an issue previously demonstrated in astrocytomas, 46 glioblastomas, 47 prostate carcinomas, 48 and colorectal carcinomas. 49…”
Section: Discussionsupporting
confidence: 62%
“…Partitioning cluster analysis (CA) based on principal components (PCs) was applied to construct a hierarchical structure in all of the Class III malocclusion individuals. We performed CA by the k-means method, which sorted participants into groups by maximizing differences and minimizing differences [26, 27]. The clustering algorithm was performed separately for a range of 3 to 6 clusters.…”
Section: Methodsmentioning
confidence: 99%
“…A minority of the resident perivascular cells was closely associated with remodeled blood vessels forming capillary loops or glomeroloid bodies 35 , further suggesting reciprocity in the perivascular niche 8,10 . Previous studies demonstrated that glomeroloid bodies are populated by stem-like tumor cells in human tumor specimen 36 and this microvascular pattern is associated with a worse outcome in patients 37,38 .…”
Section: Discussionmentioning
confidence: 94%